Penerapan Model Pembelajaran Teams Games Tournament (TGT) untuk Meningkatkan Motivasi Belajar Siswa - Lizuar Arteria Andrianto; Nisa, Ziadatun (Sekolah Tinggi Agama Islam Persatuan Umat Islam Majalengka, 2025)
Abstract This study is motivated by the low learning motivation of students in Islamic Religious Education (PAI), which is indicated by passive attitudes, low participation in discussions, and the perception that PAI material is merely rote learning and less engaging. Therefore, a learning model that can significantly increase students’ learning motivation is needed. The purpose of this study is to examine the effectiveness of the cooperative learning model Teams Games Tournament (TGT) in improving students’ learning motivation, particularly on the topic of Qurban. The TGT model was chosen because it integrates group collaboration, educational games, and healthy competition, which are expected to foster enthusiasm, responsibility, and active student engagement in the learning process. The research method used is Classroom Action Research (CAR), carried out in two cycles with 17 fifth-grade students as research subjects. The results showed a significant increase in students’ learning motivation, from 67% (high category) in the first cycle to 77% (very high category) in the second cycle. This improvement was evident in students’ enthusiasm, activeness in asking questions, participation in group discussions, and punctuality in completing tasks. Thus, the cooperative learning model TGT proved effective in enhancing students’ learning motivation in PAI, especially on the Qurban material. This study suggests that PAI teachers as well as teachers of other subjects consider implementing TGT as an innovative learning approach to create more enjoyable and meaningful learning experiences at the elementary school level.